Vaginal cytology pattern and birth features of female wistar rats treated with graded doses of ethanolic extract of spondias mombin (2012)
Twenty-five virgin female wistar rats weighing between 120g and 200g and divided into five groups of five rats per group were treated with graded oral dosages of ethanolic extract of Spondias mombin. Dosages served were 800mg/kg, 600mg/kg, 400mg/kg and 200mg/kg for groups A, B, C, D respectively and distilled water for group E which served as control. Five untreated proven male were used for copulation, one per group.Vaginal cytology was done daily for two weeks before treatment with extract to establish an oestrous cycle pattern repeated daily for another two weeks simultaneously with extract administration. Mating, pregnancy diagnosis and determination of birth parameters followed immediately after the end of extract treatment. Vaginal smears prior treatment and during treatment contained epithelial cells consistent with the different phases of estrus in the wistar rat and provided a cyclical pattern indicating that Spondias mombin had no negative effect on the estrous cycle of the wistar rat. Pregnancy and birth rates were favoured with groups A (800mg/kg) and E (control). Average litter sizes in all the groups were not significantly different. The average live birth weight of the neonates measured was observed to be highest for Group A with average live birth weight of 6.27g, followed by Groups B and the control with average live birth weight of 5.83g and 5.50g. The Groups C and D had lower average live birth weights of 4.01g and 4.74g respectively. The group A average weight was significantly high compared with other treatment groups and control (p<0.05). It was concluded that ethanolic extract of Spondia Mombin at 800mg/kg fed orally before copulation had no anti fertility effect on female wistar rat instead appeared to potentiate gestation parameters but same could not be said for dosages as low as 200mg/kg.